Adversity Quotient dalam Sinteron: Studi Perbandingan antara Indonesia dan Korea - Diyah Sulistiyorini (Fakultas Psikologi Universitas Pancasila, 2010)
Indonesian serial drama or often called sinetron has been dominated television show in Indonesia. Most television viewers spend their most time to watch sinetron. Meanwhile, there is a serious phenomenon that the number of depression has been increased throughout the world, including in Indonesia. Therefore, Adversity Quotient, defined as one's capacity to face and overcome adversity in his/her life, which stated by Stoltz, becomes necessary to discuss. There are three types of AQ: Quitters (the ones who choose to quit and ignoring the opportunity); Campers (the ones who are afraid to take risks and choose to be satisfied with what they have gained); and Climbers (the ones who do not allow anything to stop them to move forward). This was a qualitative descriptive study with non-frequentive content analysis technique to analyze the data. The samples of this study were 15 of Indonesian sinetron and 15 Korean sinetron. The samples were taken by incidental sampling technique. The result of this study demonstrated that most of sinetron's characters (62%) were categorized as Campers, 31% were Quitters, and only 7% were Climbers. Meanwhile, in KOrean sinetron, there were 56% Climbers, 36% Campers, and 8% Quitters. The conclusion was Indonesian sinetron showed less climbers characteristics than Korean sinetron. In sinetron, success was associated with religious efforts, whereas in Koream sinetron success was related with hard work and optimistic attitude.